Farmer feedback in Tricot / Redesigning the Tricot feedback process & field validation 2024- 2025 - Muller, Anna; Schumann, Charlotte; Londoño, Juan Manuel (2025)
This study documents the redesign and field validation of a farmer feedback package for the Tricot (Triadic Comparison of Technologies) methodology during 2024–2025, aimed at strengthening farmer participation and improving the communication of trial results. Using a Human-Centered Design approach, the project tested a personalized one-page feedback sheet and a participation diploma with 44 cassava farmers across five states in Nigeria. Results indicate high acceptance among farmers, with 70% rating the feedback sheet as highly useful and a Net Promoter Score (NPS) of 70.45, reflecting strong perceived value and trust. Implementers also reported improved clarity and efficiency, although challenges remain related to icon comprehension, contextual adaptation, and operational integration. Overall, the findings demonstrate that tangible, well-designed feedback artifacts can enhance trust, comprehension, and legitimacy in participatory breeding systems and support the scalable adoption of farmer-centered feedback practices.